Brief Report: Impact of Antiretroviral Regimen on Pregnancy and Infant Outcomes in Women With HIV/ HBV Coinfection. (1st September 2022) - Kiweewa, Flavia Matovu; Tierney, Camlin; Butler, Kevin; Peters, Marion G.; Vhembo, Tichaona; Moodley, Dhayendre; Govender, Vani; Mohtashemi, Neaka; Ship, Hannah; Musoke, Philippa; Dula, Dingase; George, Kathy; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: There are limited data on the impact of antenatal antiretroviral regimens (ARV) on pregnancy and infant outcomes in HIV/HBV coinfection. We compared outcomes among 3 antenatal antiretroviral regimens for pregnant women with HIV/HBV. Methods: The PROMISE study enrolled ARV-naive pregnant women with HIV. Women with HBV were randomized to (no anti-HBV)-zidovudine (ZDV) + intrapartum nevirapine and 1 week of tenofovir disoproxil fumarate and emtricitabine (TDF-FTC); (3TC)-3TC + ZDV + LPV/r; or (FTC-TDF)-FTC + TDF + LPV/r. Pairwise group comparisons were performed with Fisher exact, t, or log rank tests. Adverse pregnancy outcome (APO) was a composite of low birth weight, preterm delivery, spontaneous abortion, stillbirth, or congenital anomaly. Results: Of 138 women with HIV/HBV, 42, 48, and 48 were analyzed in the no anti-HBV, 3TC, and FTC-TDF arms. Median age was 27 years. APOs trended lower in the no anti-HBV (26%) vs 3TC (38%), and FTC-TDF arms (35%), P ≥ 0.25). More infant deaths occurred among the FTC-TDF [6 (13%)] vs no anti-HBV [2 (5%)] and 3TC [3 (7%)] arms. There were no differences in time-to-death, HIV-free survival, birth or one-year WHO Z-score length-for-age, and head circumference. Hepatitis B e antigen (HBeAg) was associated with an increased risk of APO, 48% vs 27% (odds ratio 2.79, 95% confidence interval: 1.19 to 6.67, post hoc ). Conclusion: With HBV/HIV coinfection, the risk of an APO was increased with maternal ARV compared with ZDV alone, although the differences were not statistically significant. Maternal HBeAg was associated with a significantly increased risk of APO. Infant mortality was highest with FTC + TDF + LPV/r. Early assessment of HBeAg could assist in identifying high-risk pregnancies for close monitoring.